Religiopolitical and sociocultural factors shaping creative decisions in the production of british and Malaysian Islamic television - Nur Kareelawati Abd. Karim; Ahmad A.F. (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by WOS/SCOPUS